Agile Short Unified Process – ASUP: uma metodologia híbrida apoiada na adaptação do framework scrum e do unified process - UP - França, Mauro Borges (2022)
Finding a software development methodology that is adherent to the characteristics of software projects conducted by educational institutions, whether for the areas of management, teaching, research, and extension is a great challenge for researchers. In this sense, this research presents a hybrid methodology, called Agile Short Unified Process (ASUP). The proposal is based on elements extracted from the Scrum framework inserted in the four phases of the Unified Process (UP): Conception, Elaboration, Construction and Transition. Each phase is a represented and typified life cycle with all its elements worked and generated until its end. The phases and disciplines of each cycle are integrated and in them are demonstrated the artifacts to be produced and the actors involved in their activities per phase cycle of the process. To evaluate the efficiency, the work was applied in nineteen projects with different characteristics within Higher Education Institutions. The projects were grouped with distinct characteristics, such as: Software Factories of two federal institutions of professional education (Instituto Federal do Triângulo Mineiro - IFTM and Instituto Federal do Norte de Minas Gerais - IFNMG), Junior Enterprise linked to IFTM; R&D Projects linked to the Universidade Federal de Uberlândia; Extension Projects linked to the State Public Ministry with partnership of IFTM and, finally, in academic projects linked to the discipline of Workshops of the Course of Systems Analysis and Development of IFTM. For each of the projects a table with their perceptions was presented, demonstrating their highlighted points. In one of the projects the entire process was discussed, to represent the details of the methodology. Finally, it is inferred that the adoption of the methodology has produced improvements in the practices of managing software projects, and it is noteworthy that historically, the methodologies have always emerged from other models and thus have been evolving, existing currently the Scrum, the RUP and now the ASUP.